2014
DOI: 10.1016/j.bbamem.2013.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of quercetin interactions with liposomal and vacuolar membranes

Abstract: Quercetin (3,3',4',5,7-pentahydroxyflavone) is claimed to exert many beneficial health effects. With application of (1)H NMR (nuclear magnetic resonance) and FTIR (Fourier-transform infrared) techniques, quercetin interaction with liposomes formed with dipalmitoylphosphatidylcholine (DPPC) was analyzed. Patch-clamp technique was employed to study quercetin effects at single channel level of vacuolar membranes in the liverwort Conocephalum conicum. Light and electron microscopy were applied to study quercetin e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 83 publications
8
42
0
Order By: Relevance
“…The spectral shift of band representing C=O stretching and broadening of P=O stretching vibrations relatively confirmed the binding of flavonoids to the polar head of the membrane through the oxygen groups of lipid and keto groups of flavonoids. Our results strongly support the previously reported study results, [53][54][55] where majority of the flavonoids bind to the polar heads (C-O-P-O-C stretching) of the PC via hydrogen bonding, thus indicating the localization of flavonoids. Thermal analysis behavior of PC alone (PC), flavonoids alone (QKA), physical mixture of flavonoids with carrier (QKA + PC), and M4 flavonosome (M4) was obtained by DSC and TGA ( Figure 7F).…”
supporting
confidence: 82%
“…The spectral shift of band representing C=O stretching and broadening of P=O stretching vibrations relatively confirmed the binding of flavonoids to the polar head of the membrane through the oxygen groups of lipid and keto groups of flavonoids. Our results strongly support the previously reported study results, [53][54][55] where majority of the flavonoids bind to the polar heads (C-O-P-O-C stretching) of the PC via hydrogen bonding, thus indicating the localization of flavonoids. Thermal analysis behavior of PC alone (PC), flavonoids alone (QKA), physical mixture of flavonoids with carrier (QKA + PC), and M4 flavonosome (M4) was obtained by DSC and TGA ( Figure 7F).…”
supporting
confidence: 82%
“…The current view for the localization of the three 2 compounds correlates well with most other existing studies, which suggest localization of 3 flavonoids between the boundary of the lipid/water interface and the upper half of the 4 hydrocarbon chain region. 52,53,54,55,56,57 Notwithstanding this view, some studies suggest that the 5 flavonoids partition into the hydrophobic region of the membrane. 58,59 An NMR study has 6…”
mentioning
confidence: 99%
“…54 A FTIR study suggested the same explanation 8 for quercetin. 55 Movileanu et al, 53 proposed a pH dependent insertion of quercetin within 9 membranes. Quercetin molecules inserted between the polar head groups at alkaline pH, with 10 deeper localization at acidic pH, due to intercalation of quercetin molecules between the acyl 11 chains.…”
mentioning
confidence: 99%
“…Recent studies revealed that incorporation of quercetin into the phospholipid bilayer occurs via a hydrogen bonding between its own hydroxyl groups and lipid polar head groups in the C-O-P-O-C segment. Both FTIR and NMR techniques revealed that quercetin affects the lipid bilayer in the region corresponding to alkyl chains [21].…”
Section: Introductionmentioning
confidence: 99%